Phase II, Open-Label Study of Ciltacabtagene Autoleucel, an Anti–B-Cell Maturation Antigen Chimeric Antigen Receptor–T-Cell Therapy, in Chinese Patients With Relapsed/Refractory Multiple Myeloma (CARTIFAN-1). Issue 6 (20th February 2023) - Mi, Jian-Qing; Zhao, Wanhong; Jing, Hongmei; Fu, Weijun; Hu, Jianda; Chen, Lijuan; Zhang, Yiwen; Yao, Dan; Chen, Diana; Schecter, Jordan M.; Yang, Fan; Tian, Xiaochen; et al.
Abstract : PURPOSE: CARTIFAN-1 aimed to evaluate the efficacy and safety of ciltacabtagene autoleucel (cilta-cel), a B-cell maturation antigen–targeting chimeric antigen receptor T-cell therapy, in Chinese patients with relapsed/refractory multiple myeloma (RRMM). METHODS: This pivotal phase II, open-label study (ClinicalTrials.gov identifier: NCT03758417 ), conducted across eight sites in China, enrolled adult patients with RRMM who had received ≥ 3 lines of prior therapy, including a proteasome inhibitor and immunomodulatory drug. Patients received a single infusion of cilta-cel (target dose 0.75 × 10 6 chimeric antigen receptor–positive viable T cells/kg). The primary end point was overall response rate. Secondary end points included progression-free survival (PFS), overall survival (OS), and incidence and severity of adverse events (AEs). RESULTS: As of the clinical cutoff of July 19, 2021, 48 patients received a cilta-cel infusion. At an 18-month median follow-up, the overall response rate was 89.6% (95% CI, 77.3 to 96.5), with a median time to first response of approximately 1 month; 77.1% of patients (95% CI, 62.7 to 88.0) achieved complete response or better. Medians for duration of response, PFS, and OS were not reached. The 18-month PFS and OS rates were 66.8% (95% CI, 49.4 to 79.4) and 78.7% (95% CI, 64.0 to 88.0), respectively. Hematologic AEs were common, including anemia (100%), neutropenia (97.9%), lymphopenia (95.8%), and thrombocytopenia (87.5%). Cytokine release syndrome occurred in 97.9% of patients (35.4% grade 3/4); the median time to onset was 7 days, and the median duration was 5 days. Infections occurred in 85.4% of patients (37.5% grade 3/4). Ten deaths occurred after cilta-cel infusion, eight of which were due to treatment-related AEs. CONCLUSION: These data demonstrate a favorable risk-benefit profile for a single infusion of cilta-cel, resulting in early, deep, and durable responses in heavily pretreated patients with RRMM in China.